Implementation of the legal functions of state administration in creating a good governance system in Indonesia - Mery Herlina (IHSA Institute, 2022)
Indonesia is a state based on law, where as a state based on law, every administration of government must be based on applicable law, and in a state based on law law is also placed as a rule of the game in the administration of state, government and society. While the goal of a rule of law itself is the creation of state, government and social activities that are based on justice, peace and expediency. The existence of State Administrative Law is expected to know the limits and nature of power, purpose and nature of obligations, as well as the forms of sanctions in the event of a violation of state administration. The results of this study explain that the state as an organization of power has placed a central position in the collective life of modern humans. The state is no longer only seen as an absolute entity, where all supporting stakeholders of the state must be subject to the (ruler) in a mutal manner, but, on the contrary, the state must follow the total rhythm of all elements forming the state, especially the people or citizens of the country concerned. The presence of state administrative law in the midst of society basically contains all the regulations relating to the way in which government organs carry out all their functions and duties according to the applicable authority. So we can understand that the core of this state administrative law is that it contains the rules of the game relating to the functions of government organs which can be seen in two aspects, namely state administration as an organization and administration that specifically pursues the attainment of state (public) goals set. on the basis of coercive law. However, to find out how big the consequences are, it must be understood through the eyes of the government about why this arrangement needs to be carried out so that it causes minimal consequences in its implementation.